Micro-reactive Inkjet Printing of Three-Dimensional Hydrogel Structures. (28th December 2017) - Teo, Mei Ying; Stuart, Logan; Aw, Kean C.; Stringer, Jonathan
Abstract: Inkjet printing, of the researched techniques for printing of hydrogels, gives perhaps the best potential control over the shape and composition of the final hydrogel. It is, however, fundamentally limited by the low viscosity of the printed ink, which means that crosslinking of the hydrogel must take place after printing. This can be particularly problematic for hydrogels as the slow diffusion of the crosslinking species through the gel results in very slow vertical printing speeds, leading to dehydration of the gel and (if simultaneously deposited) cell death. Previous attempts to overcome this limitation have involved the sequential printing of alternating layers to reduce the diffusion distance of reactive species. In this work we demonstrate an alternative approach where the crosslinker and gelator are printed so that they collide with each other before impinging upon the substrate, thereby facilitating hydrogel synthesis and patterning in a single step. Using a model system based upon sodium alginate and calcium chloride a series of 3D structures are demonstrated, with vertical printing speeds significantly faster than previous work. The droplet collision is shown to increase advective mixing before impact, reducing the time taken for gelation to occur, and improving definition of printed patterns. With the facile addition of more printing inks, this approach also enables spatially varied composition of the hydrogel, and work towards this will be discussed.